The Fleet of Air Carriers Operating in Regular Traffic on the Polish Market - Structure, Trends, Challenges - Melski , Krzysztof (Studia Oeconomica Posnaniensia, 2016)
A fundamental tool for achieving the business goals of an airline is the aircraft used by the airline, usually airliners. With the current possibility to obtain an airliner, in reasonable condition (model and version of the airplane, delivery time, financial conditions), the fleet determines all areas of the business activity for the airline. Intensive growth of the number of passengers generates an unprecedented demand for new planes, especially in the segment of single aisle airliners, which are the basis of the most airline fleets. Despite the steady growth production of the aircraft industry, further production of the most popular single aisle is still delayed by 6-9 years. The current plans of airliner producers and the long duration of design and certification processes suggest that a new model will not appear within the next 15 years. Consequently, changes in the airline’s fleet will be more qualitative than quantitative. The present and projected destinations of airlines in the Polish market need to apply for regional and one aisle middle range airliners. The contribution of turboprop machines will slowly decrease, while the long range, wide-body machines remain negligible. The high inertness of the new passenger aircraft market and the limited availability of relatively modern, cost-effective and eco-friendly airlines on the secondary market determines an airline’s fleet policy. It significantly limits the flexibility of the current operations and development of the airline. The long period of time and the costly process of the acquisition/replacement of part or all of the fleet is high-risk. Success depends on many factors: changes in the air transport market, competition between air carriers, availability of new airliners, worldwide and local political and economic circumstances. Slow, long-term planned changes of the airline’s fleet gives: airports, handling agents, service and maintenance of aircraft facilities, training of the staff units, and possibilities of long-term development.